ICT Application in Organizing Faculty Exchange Programs: A Case Study - Anh Thi Phuong Le; Huyen K. Pham; Nguyen Thi Thao Ho (Acta Pedagogia Asiana, 2026)
The global advancement of information and communication technology has had a significant impact on faculty exchange programs, among other areas of higher education institutions. Using the virtual method in faculty exchange programs between a higher education institution and its foreign partnerships is one way to adapt to the current state of development in the teaching and learning environment. Through an analysis of the program's implementation in a Vietnamese institution, this paper aims to illustrate how virtual faculty exchange programs’ organization has evolved. The case study and action research approach are used to analyzed a Vietnamese higher education institution (HEI)’s faculty exchange programs with its international partners from 2019 to 2023, seeking to ascertain the most suitable institutional adjustment for overseeing and growing such endeavors. Although this study is restricted to the viewpoint of a Vietnamese university, it offers an illustration of how faculty exchange programs are implemented and promoted in numerous higher education establishments worldwide.